HUBUNGAN KONFORMITAS DAN HARGA DIRI DENGAN PERILAKU KONSUMTIF PADA REMAJA PUTRI DI KOTA DENPASAR - Made Indah Yuliantari; Yohanes Kartika Herdiyanto (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2015)
Female teenager conformity behavior is caused by several factors, which is internal factor and external factor. One of the internal factor that caused female teenager has consumptive behavior is prestige. In the other hand, having a low prestige makes female teenager tense to make friends and join a certain group in accordance to lifting their prestige. There is a conformity factorin a teenager group. That result in one’s behavior which is based on their mate in that group. Because they want have a same norms which is expected with their group (Sarwono, 2002). If they can’t control consumptive behavior, it will give them bad impact such as wasteful, unproductive, a crime where a person will do something. On the other hand teenager is stage where a person tries to find their own identity through their friend of the same age. This will be very much related to conformity and self esteem female teenager consumptive behavior in Denpasar. There is a positive relationship between conformity and female teenager consumptive behavior and also there is a negative relationship between self esteem and female teenager consumptive behavior in Denpasar. This study was used quantitative method. There were 286 female teenager start from 10 and 11 grade student in Denpasar senior high school. They were selected by stratified random technique sampling. The data was obtain by using conformity scale (Reliability alpha 0,901), self esteem scale which was adopted by Wardhani (2009) (Reliability alpha 0,939), and consumptive behavior scale (Reliability alpha 0,900). The result of this study was showed there was a significant relationship between conformity and self esteem female teenager consumptive behavior in Denpasar (R=0,407; r2=0,165), by using multiple regression analysis. Partially there was a positive significant relationship between conformity and teenager consumptive behavior in Denpasar (r= 0,408); and also there was negative significant relationship between self esteem and female consumptive behavior in Denpasar (r= -0,124). Keyword: Conformity, Self Esteem, Consumptive Behavior.